Consumer Behavior in the Era of Digital Marketing: Trends and Challenges - Haile Gebrselassie; Abebe Bikila; Derartu Tulu (Proceeding of The International Conference on Economics and Business, 2024)
Digital marketing has revolutionized how businesses interact with consumers. This paper examines emerging trends in consumer behavior, such as personalization and social media influence, and addresses challenges like data privacy and trust. Recommendations for effective digital marketing strategies are provided.